The Impact of COVID-19 on Higher Education in South Korea - Csizmazia, Roland A. (Innovare Journal of Education, 2023)
The COVID-19 pandemic forced universities worldwide to switch from face-to-face teaching to online remote teaching. The majority of students are dissatisfied as their college lives are completely ruined, and they are not able to maintain their social networks. South Korean higher education has long been troubled by decreasing tuition revenues, an aging problem, the low-level internationalization of university education, and administrative redundancies, and now the pandemic has greatly aggravated these structural defects. Furthermore, course content creation posed a major challenge to professors, while the lack of student motivation and commitment led to a rapid decline in the quality of education and evaluation. Accordingly, students requested a refund of their tuition fees, or at least compensation, and called for the improvement of online courses.